THE ROLE OF NURSING PRACTICE IN MODERN HEALTHCARE: CHALLENGES AND OPPORTUNITIES - Alimjonova Oynura Shukurali qizi, (TADQIQOTLAR, 2025)
Abstract Nursing is a cornerstone of healthcare systems worldwide, playing a pivotal role in  patient  care,  advocacy,  and  education.  This  paper  explores  the  fundamental responsibilities of nurses, their contributions to healthcare delivery, and the challenges they face. It also emphasizes the importance of continuous professional development and policy support to enhance nursing outcomes globally.